Estimasi Cadangan Karbon Tersimpan pada Ekosistem Hutan Mangrove di Desa Kurau Timur, Kabupaten Bangka Tengah - Henri, Henri; Syafa'ati, Rizqy; Farhaby, Arthur Muhammad (Jurnal Hutan dan Masyarakat, 2023)
The mangrove forest ecosystem in East Kurau Village is a 148-hectare area that has the potential to reserve carbon. This research aims to identify the composition of mangrove vegetation types and analyze the potential for carbon stocks reserved in tree stands and sediments in the mangrove forest area in East Kurau Village. The method used to identify the composition of the mangrove vegetation types is a 10m x 10m plot. The tree biomass measurements were implemented using the no-logging method using allometric equations. The measurement of the sediment analysis was using Walkley & Black method. The result of the mangrove types composition in the East Kurau Village mangrove forest ecosystem consisted of 6 genuine/true species: Sonneratia alba, Rhizophora apiculata, Xylocarpus granatum, Acrostichum aureum, Bruguiera gymnorrhiza, and Bruguiera hainesii. The estimated carbon reserves in East Kurau Village's mangroves are 3.207, 29 tons/ha. The mangrove tree biomass of 57.966,57 kg/m2 and 18,44 % on the percentage of carbon content in the sediments.